STRATEGI MEMBELAJARKAN MATEMATIKA PADA KELAS VII INKLUSI DI SMP PGRI 1 SAMPIT KABUPATEN KOTA WARINGIN TIMUR - Shaliha, Nurul Hidayati; Kusmayadi, Tri Atmojo; Sujadi, Imam (Jurnal Pembelajaran Matematika, 2015)
Abstract: The objectives of this research were to describe inclusive learning system and teacher strategy in teaching mathematics from the teacherâs ability in explaining in accordance with conceptual and procedural knowledge of 7th grade students of SMP PGRI 1 Sampit. This research was a qualitative descriptive using a single case study method, in depth study of learning system and Mathematics learning in inclusive school. The subject of the research was the Headmaster of SMP PGRI 1 Sampit to obtain information about learning system and Mathematics teacher assistant of the 7th grade in order to know the Mathematics learning strategy in inclusive class of SMP PGRI 1 Sampit. The information of inclusive learning systems were taken by documenting, observation and interview. The validity technique of learning system data used in this research was Triangulation Method. The information of Mathematics learning strategy including the teacherâs ability in explaining the conceptual and prosedural knowledge. The data was taken from the transcription of six recording Mathematics learning activity and two best observations. The validity technique of learning system data used was member check technique. The research result shows as follows : 1) The learning system of inclusive students of the 7th grade of SMP PGRI 1 Sampit was different with the regular learning system. However, it was found that there is no individual learning program especially for slow learner students and the lack of computer technology used in the learning process. 2) The Mathematics learning strategy in the inclusive 7th grade of SMP PGRI 1 Sampit observed from the teacherâs ability in explaining the subject in accordance with the delivering explanation indicators which were planning the explanation, clarity of delivering the explanation, the use of examples and illustrations, the use of intonation in delivering the explanation, and giving the feed back to the students. The teacher used Contextual Teaching and Learning (CTL) to teach the concept of mathematics and Discovery Learning methods to teach the procedure of mathematics.Keywords: learning system, Mathematics learning strategy, inclusive